2012
DOI: 10.4103/2231-0762.109364
|View full text |Cite
|
Sign up to set email alerts
|

Do the more caries in early primary dentition indicate the more caries in permanent dentition? Results of a 5-years follow-up study in rural-district

Abstract: Aim:In the deprived communities with high caries incidence, determination of high-risk children in early age is a valuable tool to apply the individual and/or community-level preventive measures. The purpose of this 5-years follow-up study was to examine the relationship between early caries occurrence on primary incisors and the future caries occurrence on both first permanent molars and all permanent dentition in the children living in rural Turkey.Materials and Methods:Total 34 children living in rural-dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…[101718] From this study, it is clear that awareness regarding bad practices is abundant which is indicated by the low prevalence, i.e. 18.5% approximately.…”
Section: Discussionmentioning
confidence: 99%
“…[101718] From this study, it is clear that awareness regarding bad practices is abundant which is indicated by the low prevalence, i.e. 18.5% approximately.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the young age of the children, S-ECC is difficult to treat successfully in the dental chair [7–9] and these children frequently require treatment under general anaesthesia [10] which increases treatment costs [11]. S-ECC is a risk factor for caries of permanent teeth [1214] and affected children are at a higher risk of developing recurrent caries [8, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are conceptual limitations in previous SEM studies. First, although dental problems in primary teeth lead to future dental caries in permanent teeth [al-Shalan et al, 1997; Dulgergil and Colak, 2012], most path model studies have used children's carious permanent teeth instead of carious primary teeth. Second, most path model studies tested children's behavior as a mediator for their oral health outcomes, but they did not consider caregiver's behavior, even though parental behavior impacts child oral health behavior [Hooley et al, 2012].…”
Section: Introductionmentioning
confidence: 99%